Record Linkage for Historical German VET Data : Towards Linked Labor Market Data - Reiser, Thomas [Verfasser]; Dörpinghaus, Jens [Verfasser]; Steiner, Petra [Verfasser] (My University, 2025)
"Digital archives often describe their catalogs with digital objects where each record represents a physical document that can be found in the archive. While this is approach is most effective to describe data that is present in the archive, there are some archives where the absence of missing documents can impact its quality. To approach methods that can be used to assess the completeness of an archive, we use record linkage methods on the example of the occupations archive at the Federal Institute for Vocational Education and Training (BIBB), combined with the genealogy of vocational education. Our idea is that every record from the genealogy – which describes the history of vocational training in Germany – should have a matching record in the occupations archive – which contains the legal regulations that build the foundation for the genealogy – which implies a mapping between the two data sets. To this end, we create pairs of potential matches between records of both data sets and separate them in two classes: matches and non-matches. These pairs are then used to train different classifiers that should be able to categorize unseen record pairs. The results show that the the selected classifiers give reasonable results but need some more improvements for better reliability." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; G 2.2.1 Technologisierung; 370; Berufsbildungsforschung; Archiv; Digitalisierung; Klassifikation; Textanalyse; Texterkennung